Don Bosco and the Conditions of Pre-industrial Youth in His Times - Joseph Boenzi (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The year 2015 marks the bicentenary of the birth of Saint John Bosco, whom Pope John Paul II designated as the father and teacher of youth. As members of the Salesian Family worldwide comme- morate this event, they do so with the intention of starting afresh in the spirit of this saint to promote and foster the education of young people in our times - especially the poorest and most in need. But who are the young people that Don Bosco would most try to educate today? What was the situation of adolescents and young adults in his lifetime? - those the he actually encountered? This paper at- tempts to survey the social, political, cultural and religious context of the young of Don Bosco's city of Turin in the middle nineteenth century. My hope is to present reflections that can help us to reflect or study or even share in groups on Don Bosco's young people and our own. For, according to Don Bosco, the young are that portion of human society that is the most delicate and the most precious, on which so many hopes for a happy future are placed.